2021
DOI: 10.14814/phy2.14788
|View full text |Cite
|
Sign up to set email alerts
|

β‐endorphin differentially contributes to food anticipatory activity in male and female mice undergoing activity‐based anorexia

Abstract: Anorexia nervosa (AN) has a lifetime prevalence of up to 4% and a high mortality rate (~5–10%), yet little is known regarding the etiology of this disease. In an attempt to fill the gaps in knowledge, activity‐based anorexia (ABA) in rodents has been a widely used model as it mimics several key features of AN including severely restricted food intake and excessive exercise. Using this model, a role for the hypothalamic proopiomelanocortin (POMC) system has been implicated in the development of ABA as Pomc mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…It has been suggested that the runner’s high results from the stimulation of endorphins via opioid signaling during exercise 33 . In female ABA mice, transiently increasing levels of proopiomelanocortin RNA and peripheral β‐endorphin levels have been detected 34 . These findings could partially explain the association between running and reduced anxiety‐related behavior observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…It has been suggested that the runner’s high results from the stimulation of endorphins via opioid signaling during exercise 33 . In female ABA mice, transiently increasing levels of proopiomelanocortin RNA and peripheral β‐endorphin levels have been detected 34 . These findings could partially explain the association between running and reduced anxiety‐related behavior observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Future studies using knockout models (e.g., Daimon & Hentges, 2021) targeting opioid and catecholamine receptors will hopefully provide information regarding the role of these systems in reinforcing exercise under the ABA model. Additionally, animal models may inform the development of medications to treat pathological exercise, similar to research in alcohol and substance use disorders (Spanagel, 2017).…”
Section: Continued Use Of Animal Modelsmentioning
confidence: 99%
“…Therefore, it appears that starvation increases the orexigenic signaling, consistent with previous literature that reports an increase in Npy expression [ 18 , 19 ]. Previous studies revealed conflicting results regarding the Pomc expression [ 18 , 21 , 22 ]. In ABA rats, there was an increase in the density of POMC + cells in the ARC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food intake-related pathways may be involved in starvation, as evidenced by the upregulation of Npy and Agrp mRNA expression in an activity-based anorexia (ABA) model which includes a limited time for feeding [ 18 20 ]. However, the results for Pomc mRNA expression have been conflicting, as two studies demonstrated an increase in Pomc expression in the arcuate nucleus (ARC) in ABA animals, whereas one study reported a decrease in Pomc expression [ 18 , 21 , 22 ]. In addition, the POMC + cell densities in the ARC in ABA animals were increased [ 23 ].…”
Section: Introductionmentioning
confidence: 99%